Impact of air pollution on forest stands in the vicinity of Wodzisław Śląski and Rybnik, Poland - Barniak, Joanna; Jureczko, Agnieszka (Geology, Geophysics and Environment, 2020)
Tree-ring analysis was used to investigate the impact of air pollution on forest stands in southern part of the Upper Silesia region of southern Poland. Four about 120 years old Scots pine stands located near Wodzisław Śląski and Rybnik were selected for study and 20 increment core samples from each stand were taken. All study stands were selected based upon their considerable exposure to air and dust pollution. The results of dendrochronological analysis showed strong and significant reductions in tree ring growth especially during the period from 1960 to 1990. A significant number of trees with reductions (85%) was observed in two Scots pine stands both of which are directly exposed to air pollution from mine-owned coking plant and power and heating plants. Since 1990s the improved growth of these pines was clearly noted. A comparison for the period 1970 to 1990 for stands located west from the main emitters’ versus stands east and directly exposed found fewer trees with growth reductions (ca. 40%). At the beginning of the 21st century, a large number of trees in these western stands were observed with growth reductions between 50 and 60%. Probably, these trees were affected by air pollution from a nearby power plant located immediately across the border in the Czech Republic. Relationships between periods of severe reductions in ring width growth or missing rings were noted in a large percentage of pine trees in all four stands; these cross-stand relationships suggested common weather related impacts. Missing rings were noted in 1956, 1963, 1968, 1970, 1971, 1973, 1976 and 1979.